EXPLORING EFL VOCATIONAL STUDENTS IN BOOK TALK STRATEGY IN READING COMPREHENSION: A CASE STUDY - Annisa Ryani Fitri; Kusrin Kusrin; Abdul Kodir Al-Baekani (PROJECT (Professional Journal of English Education), 2023)
In reading classes, students were emphasized learning through tests, e.g., multiple choice and essays. They needed more opportunities to own and assign reading-discussion activities to help with these weaknesses. This study aims to determine the phases to assist students in understanding the text using the book talk strategy and to know students’ responses toward the book talk strategy. This study used a qualitative and case study design to conduct this research. The researcher conducted observations, reflective journals, and semi-structured interviews to collect data. The data analysis used in the research adopts the thematic analysis from Braun & Clarke. The study showed three phases in conducting the book talk strategy in the reading classroom: selecting literature, students’ discussion, and students’ presentation. Most students were happy and enjoyed during the lesson. They are active in the discussion and easily comprehend the text. All of them were students’ responses about the book talk strategy in the reading classroom. The study highlights the students’ engagement appeared in this strategy. The student’s engagement included three aspects, e.g., affective, behavioral, and cognitive. The implication is an increased understanding of student involvement in learning and the use of exciting book talk strategies in reading classes.